Comparison of Sertraline with Rifampin in the treatment of Cholestatic Pruritus: A Randomized Clinical Trial - Ataei, Sara; Kord, Leila; Larki, Amir; Yasrebifar, Fatemeh; Mehrpooya, Maryam; Seyedtabib, Maryam; Hasanzarrini, Maryam (Reviews on Recent Clinical Trials, 2019)
Background: Pruritus is one of the most common and disabling symptoms of liver disease such as Primary Sclerosing Cholangitis and Primary Biliary Cholangitis. Cholestyramine, rifampin, opioid antagonists, antihistaminic agents and SSRIs are used for the management of pruritus. Due to rifampin drug interactions as well as its serious side effects such as hepatotoxicity, clinicians are endeavoruing to find a safer and a more effective substitution. Objective: The purpose of this study was to compare the efficacy and safety of sertraline with rifampin in the management of cholestatic pruritus. Methods: In a single-blinded randomized clinical trial a total of 36 patients of PSC and PBC were divided into two equal groups, one group received 100 mg/day sertraline and the other group received rifampin 300 mg/day for 4 weeks. Visual analog scale was used to record pruritus severity at baseline and 4 weeks after drug intervention, also, ALT, AST, ALP and total bilirubin of all patients were measured at three different time points. Results: Over the follow-up period, pruritus had relieved in both groups, but there was no significant differences between sertraline and rifampin in pruritus management (pvalue=0.740), also there was no significant difference between the two intervention strategies (A versus B) in total bilirubin level (pvalue=0.106). Moreover, the ALT, AST and ALP levels were found to be significantly different between the two groups (Pvalue#130;0.01). Conclusion: There is no difference between sertraline and rifampin in pruritus improvement, but sertraline has less adverse effects on hepatobiliary enzyme levels, so it seems to be safer than rifampin.
Keywords: pruritus